2006
DOI: 10.1063/1.2201474
|View full text |Cite
|
Sign up to set email alerts
|

The physics of vortex merger: Further insight

Abstract: Results of numerical simulations provide further insight on the physical mechanisms associated with symmetric vortex merger. The relative contributions of filament and exchange band fluid to the reduction in the vortex separation are determined and the latter is found to be dominant. A key underlying process is the interaction of strain rate and vorticity gradient near the center of rotation, through which a tilt in the vorticity contours is established. This leads to the entrainment of core fluid into the exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…This definition is in line with the definitions in Refs. [17][18][19]. It should not be confused with the definition the blob community [20] use.…”
Section: Coherent and Noncoherent Structuresmentioning
confidence: 99%
“…This definition is in line with the definitions in Refs. [17][18][19]. It should not be confused with the definition the blob community [20] use.…”
Section: Coherent and Noncoherent Structuresmentioning
confidence: 99%
“…For this reason, a number of studies have been devoted to the understanding of the key mechanisms of this process. [3][4][5][6][7][8] Previous experimental and numerical studies 3,[9][10][11][12][13][14][15] have shown that two identical vortices merge if their initial intercentroid distance is smaller than some critical value, leading to a vortex larger in size than the original vortices. It was also shown that the interaction of unequal corotating vortices is much richer than that of equal vortices.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the vicinity of the hyperbolic points, and in particular the central hyperbolic (CH) point where mutual interaction strengthens ∇ω amplification (Fig. 2-light shading near center is P s > 0), the dynamics of ∇ω and S eventually produces a tilt in ω contours [1]. At the outer hyperbolic points, this initiates filamentation.…”
Section: Introductionmentioning
confidence: 99%
“…The determination of (a/b) cr has been the focus of a number of studies, e.g., [11,10,9]. The physical mechanisms of symmetric merger have also been considered, e.g., [7,8,4,13,1,2]. In the more general interaction of two unequal size and/or strength (asymmetric) vortices, there is a greater range of flow behavior and the interaction may result in the destruction of the smaller/weaker vortex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation